2021
DOI: 10.1038/s41420-021-00401-7
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose metabolism involved in PD-L1-mediated immune escape in the malignant kidney tumour microenvironment

Abstract: Programmed death receptor-ligand 1 (PD-L1) plays a crucial role in immune evasion by tumour cells. Most tumour cells exhibit energy dependency and acquire energy from glycolysis. However, the relationship between glucose metabolism and PD-L1 expression remains unclear. In this study, changes in PD-L1 expression in renal carcinoma cells were evaluated during glucose deficiency and recovery, and PD-L1 could inversely regulate glycolysis. In addition, the possible signalling pathways activated by a low level of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…In future studies, the relationship between metabolic reprogramming and tumor immune escape should be fully considered to optimize therapy and avoid problems, such as off-target immunity, drug resistance, and possible metastasis, and the ineffectiveness of targeted metabolic therapy. The targeting of glucose metabolism and glutamine metabolism may directly regulate the expression of PD-L1 in tumor cells ( 36 , 61 ), which modulate the effects of targeted metabolic therapy because it may cause tumor immune escape. Therefore, the combined use of targeted glucose or glutamine metabolic therapy and PD-L1 ICIs may induce a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies, the relationship between metabolic reprogramming and tumor immune escape should be fully considered to optimize therapy and avoid problems, such as off-target immunity, drug resistance, and possible metastasis, and the ineffectiveness of targeted metabolic therapy. The targeting of glucose metabolism and glutamine metabolism may directly regulate the expression of PD-L1 in tumor cells ( 36 , 61 ), which modulate the effects of targeted metabolic therapy because it may cause tumor immune escape. Therefore, the combined use of targeted glucose or glutamine metabolic therapy and PD-L1 ICIs may induce a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is a negative immunoregulator that is regulated by glycolysis in many tumors. In vitro experiments found that a reduction in glucose content in the culture medium upregulated the expression of PD-L1 in renal cancer cells via the EGFR/ERK/C-Jun pathway ( 36 ). The expression of PD-L1 correlated with the uptake of 18 F-FDG in lung adenocarcinoma ( 37 ).…”
Section: Mechanism Of Glucose or Glutamine Metabolism-targeting Therapy And Pd-1/pd-l1 Checkpoint Blockade Immunotherapy Combinations Formentioning
confidence: 99%
“…Apart from this, PD-L1 and glycolysis have been shown to be positively correlated, although it is currently unclear whether PD-L1 expression enhances glycolysis or vice versa. One study has shown that glucose deprivation lead to an up-regulation of PD-L1, while siRNA knockdown of PD-L1 likewise decreased expression of glycolysis enzymes (specifically PFKFB3) in NSCLC cell lines ( 95 ). Further, another investigation found that PD-L1 increased expression of the glycolysis enzyme HK2 in SCC NSCLC ( 96 ).…”
Section: Nutrient Competition and The Tumor Microenvironmentmentioning
confidence: 99%
“…Further, another investigation found that PD-L1 increased expression of the glycolysis enzyme HK2 in SCC NSCLC ( 96 ). These studies suggest that PD-L1 may be directly involved in the up-regulation of glycolysis and elude to potential signaling mechanisms such as PI1K/AKT/mTOR, EGFR, and HIF-1α ( 95 – 98 ). Interestingly, other investigations have concluded that the metabolic switch towards glycolysis is essential for PD-L1 overexpression ( 99 , 100 ).…”
Section: Nutrient Competition and The Tumor Microenvironmentmentioning
confidence: 99%
“…Glucose deficiency could reduce the energy produced by glycolysis pathway and promote downstream ERK/c‐Jun phosphorylation by activating EGFR, thereby enhancing PD‐L1 expression. 90 In high‐grade RCC, glucose‐converted glutamine is used to alleviate oxidative stress via the glutathione pathway, and the grade of RCC was positively correlated with the expression of glutamine depletion signature. 91 , 92 Glutamine deprivation has been demonstrated to induce PD‐L1 expression by stimulating the EGFR/ERK/c‐Jun signaling pathway.…”
Section: Mechanisms Of Pd‐l1 Expression Alterations In Rccmentioning
confidence: 99%